2010
DOI: 10.1149/1.3267882
|View full text |Cite
|
Sign up to set email alerts
|

Optical Spectra and Direct Optical Transitions in Amorphous and Crystalline ZnO Thin Films and Powders

Abstract: Comparative studies of ZnO crystalline and amorphous thin films and nanocrystalline powders are reported. The UV-visible optical spectra were analyzed with special attention paid to the direct optical bandgap. Atmospheric radio-frequency barrier torch discharge and pulsed hollow cathode sputtering techniques for the film fabrication were used. For the crystalline films, similar values of the direct optical bandgap were found independent of the growth method used. The analysis of the amorphous films and powders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…With increasing ZnO thickness from 20 nm to 80 nm, such a local reflectance minimum becomes less significant. A previous study has reported that refractive index of sputtered ZnO thin film are different when deposited on different substrates [ 18 ]. E. Moulin et al concluded that for thin film silicon solar cells with a Ag BR structure, dielectric material with a lower refractive index between Ag and active silicon thin films results in lower optical losses in BRs [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With increasing ZnO thickness from 20 nm to 80 nm, such a local reflectance minimum becomes less significant. A previous study has reported that refractive index of sputtered ZnO thin film are different when deposited on different substrates [ 18 ]. E. Moulin et al concluded that for thin film silicon solar cells with a Ag BR structure, dielectric material with a lower refractive index between Ag and active silicon thin films results in lower optical losses in BRs [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…From Figure 3 b, when a thicker ZnO was deposited on top of Ag, with the increasing thickness from 120 nm to 140 nm to 160 nm, reflectance minimum shifts from 400 nm to 430 nm to 470 nm. By using the refractive index of crystalline ZnO on metal from reference [ 18 ], we can calculate the condition of destructive interference using λ_destructive = (2 × n _ZnO × t _ZnO × cos (7°))/( m − 1/2) where m = 1 for the first and m = 2 for the second destructive interference respectively. At 120 nm ZnO thickness, by using n_ZnO = 2.46 at 400 nm wavelength [ 18 ] (where we suspect 400 nm is the 2nd destructive inference), the calculated λ_2nd_destructive at m = 2 is 390 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For advanced optoelectronics and bandgap engineering applications is important to investigate the relationship between the microstructure, sample preparation conditions & optical properties. SE gives opportunity to detect technologically and scientifically important properties of thin films such as optical bang gap (Dejneka et al, 2010), thermooptical properties (Aulika et al, 2007 and2009;Dejneka et al, 2009), and optical gradient (Aulika et al, 2008 and2009;Deineka et al, January, 2001). …”
Section: Spectroscopic Ellipsometrymentioning
confidence: 99%